k-Zumkeller Labeling of Graphs - J. Balamurugan, B.; Thirusangu, K.; G. Thomas, D.; J. Murali, B. (International Journal of Engineering and Technology, 2018)
In this paper, we mainly focus on to prove that the graphs, viz., (i)paths, (ii) comb graphs, (iii) cycles, (iv) ladder graphs and (v) PnÂ´Pn graphs are k-Zumkeller graphs.Â Â